Strategi Pengembangan Ekonomi Berbasis Potensi Lokal melalui Pemberdayaan Perempuan dan Pengembangan UMKM di Desa Geneng - Ahmad Anif; Reikha Habibah Yusfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Developing Regional Economic Development through women empowerment is an effort by the Geneng Village Governmet to develop MSME. However, Regional Economic Development through women empowerment for developing MSME has not run optimally. For optimizing Regional Economic Development especially MSME which moved by women, The Geneng Village Government held an MSME’s training program. This study aims to analyze the role of the government in Geneng Villahe, MSME actors, especially women. Researcher used a descriptive qualitative approach method. Researcher conducted observations, interviewsm and documentation of MSME actors in Geneng Village especially women. This study focuses on exploring the opportunities and strategies taken in utilizing the local potential in Geneng Village. The data used are primary data and secondary data. The research subjects used included: the head of village (1 person), village officials (2 people), MSME’s (5 People) and core members of BUMDes (3 people). Thus, the total number of informant subjects is 11 people.